The Influence of Educational Media Via Youtube Social Platform on The Interest in Selecting an Intrauterine Device (IUD) Contraceptive - Pramiswari, Elya Dwi Saskia; Isfentiani, Dina; Ginarsih, Yuni; Handayani, Aris (Jurnal Ilmiah Kesehatan, 2025)
Intrauterine Device Contraception (IUD) is one of the Long-Term Contraceptive Methods (MKJP, which tends to be low. YouTube can be a valuable social media platform for accessing information about IUD contraception. The objective of this study is to assess how educational content on YouTube influences interest in selecting intrauterine device (IUD) contraception. This research used a one-group pretest-posttest design with a sample of 60 respondents, and the sampling technique used was purposive sampling. This research instrument uses a questionnaire with Wilcoxon signed-rank test data analysis. Drawing from the findings of the Wilcoxon Signed Rank Test, there was an influence before and after providing educational media via YouTube on interest in choosing intrauterine device (IUD) contraception among couples of childbearing ages. This study indicates that educational content on YouTube increases the interest of couples of childbearing ages in choosing intrauterine device (IUD) contraception.